Analisis Tantangan dan Peluang Digitalisasi untuk Penanganan Kesehatan Mental - Nur Rifkikah; Nopi Nopi; Masdiana Mustari (Media Literasi Indonesia, 2025)
The advancement of digital technology has had a significant impact on mental health, presenting both challenges and opportunities. This study aims to analyze the influence of digitalization on mental health and to explore strategies that can minimize its risks while maximizing its benefits. This research applied a literature review method using a qualitative approach by analyzing five relevant and recent academic sources. The results show that digitalization contributes to increasing cases of mental health issues such as anxiety, depression, and stress, particularly among adolescents. Nevertheless, it also offers positive opportunities including access to online mental health services, the enhancement of digital literacy, and the integration of spiritual values through digital media. Health literacy, character education, and religious-based approaches have been found effective in strengthening mental resilience in the digital age. In conclusion, digitalization must be managed wisely and collaboratively in order to optimize its role in supporting the mental well-being of Indonesian society